Strategic coopetition in parking system: A game theory analysis of shared parking platforms - Jian Li; Qian Zhao; Jiafu Su (Alexandria Engineering Journal)
The shared parking platform alleviates the insufficient supply of public parking, but it may also lead to competition with the public parking lot. To relieve the negative impact of competition, the public parking lot has a choice to partially cooperate with the platform, leading to a coopetition relationship. Purpose: This study examines the competition and coopetition dynamics between a shared parking platform and a public parking lot. Method: We apply game-theoretic models to analyze the strategic interactions between these two entities under competition and coopetition scenarios. Results: Our analysis reveals that when the inconvenience cost is low, cooperation is likely to occur. Shared parking platforms can incentivize public parking lots to participate by offering financial subsidy. As the quantity of idle private parking spaces and inconvenience cost increases, the willingness to cooperate between the two parties grows. However, this willingness first increases and then decreases as the demand rises. Conclusions: Compared to the competition scenario, private parking space owners in the coopetition scenario experience lower revenue and consumers face reduced surplus. However, both the shared parking platform and the public parking lot benefit from higher profits, and social welfare is greater in the coopetition scenario when the inconvenience cost is high, whereas the opposite is true when such cost is low.